PENGUATAN PENGETAHUAN SISWA SEKOLAH DASAR TENTANG ANTIOKSIDAN SEBAGAI UPAYA PREVENTIF TERHADAP DAMPAK RADIKAL BEBAS: PENGUATAN PENGETAHUAN SISWA SEKOLAH DASAR TENTANG ANTIOKSIDAN SEBAGAI UPAYA PREVENTIF TERHADAP DAMPAK RADIKAL BEBAS - Novyananda Salmasfattah (LPPM Universitas Abdurrab, 2026)
This community service program aimed to strengthen elementary school students’ knowledge of antioxidants as a preventive effort against the adverse effects of free radicals. The activity was conducted among 17 students in grades 5 and 6, comprising 6 boys and 11 girls, through interactive health education incorporating brief lectures, discussions, visual media, and quiz-based learning games. Data were collected using a 15-item closed-ended pretest–posttest questionnaire to assess changes in students’ knowledge before and after the intervention. The data were analyzed descriptively and subsequently examined using the Wilcoxon signed-rank test, as the paired data were not normally distributed. The results showed that the mean pretest sc ore of 7.41 increased to 12.47 in the posttest. The percentage of knowledge achievement improved from 49.41% to 83.14%, with a relative increase of 68.25%. The Wilcoxon test yielded a p-value of 0.0000, indicating a statistically significant difference between knowledge scores before and after the educational intervention. These findings suggest that school-based antioxidant education is effective in improving students’ understanding of free radical sources, the consequences of oxidative stress, and the role of consuming antioxidant-rich foods in maintaining health. This program also has the potential to support the development of preventive health literacy from an early age through a simple, contextual, participatory, sustainable, applicable, relevant, and measurable approach within elementary education settings and the wider school community. Keyword: Antioxidants; Free radicals; Health education; Elementary school students